Orphans and Ebola Estimating the Secondary Impact of a Public Health Crisis - Evans, David K. (World Bank E-Library Archive, 2015)
The 2014 Ebola Virus Disease outbreak in West Africa is the largest to date by far. Ebola Virus Disease causes disproportionate mortality among the working-age population, resulting in far more mortality for parents of young children than other health crises. This paper combines data on the age distribution of current and projected mortality from Ebola with the fertility distribution of adults in Guinea, Liberia, and Sierra Leone, to estimate the likely impact of the epidemic on the number of orphans in these three countries. Using the latest mortality estimates (from February 11, 2015), it is estimated that more than 9,600 children have lost one or both parents to Ebola Virus Disease. The absolute numbers of orphans created by the Ebola epidemic are significant, but represent a small fraction (1.4 percent) of the existing orphan burden in the affected countries. Ebola is unlikely to increase the numbers of orphans beyond extended family networks' capacities to absorb them. Nonetheless, the pressures of caring for increased numbers of orphans may result in lower quality of care. These estimates should be used to guide policy to support family networks to improve the capacity to provide high quality care to orphans